The relationship between strategic management practice and leadership: a bibliometric analysis - Khairun Sofia Awang Amit; Suddin Lada; Rudy Ansar; Brahim Chekima; Mat Salleh Ayub (Penerbit UMS, 2022)
Objective: The objective of this study was to identify the relationship between strategic management practices and leadership. A comprehensive analysis was conducted highlighting the contribution of the role of leaders in strategic management. Research methodology: This study uses the Scopus database for article searches or literature reviews. For data analysis such as systematic literature review and bibliometric, the reviewer used Excel and VOSviewer. A total of 110 articles were successfully collected from the Scopus database. Findings: The results show that the relationship between strategic management practice and leadership is related to each other. Then, 2019 was the year with the most published articles related to the field of study. Not only that, but the researcher also analysed the top 10 most published journals and most cited papers. Conclusion: Based on the results of the study, it can be concluded that strategic management and leadership are intertwined ideas that give a firm a competitive advantage.